2016
DOI: 10.1167/iovs.16-20644
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of ICOS and ICOS Ligand in Corneal Transplantation and in Maintenance of Immune Privilege

Abstract: The expression of ICOSL in the cornea and the ICOS-mediated induction of Foxp3+ CD4+ regulatory T cells may contribute to successful corneal allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…To further elucidate the mechanism of immune privilege for corneal transplantation, further immunologic analysis will be necessary. The cornea constitutively expresses various immune-regulating molecules, such as B7-H1, 8 CD95L, 35,36 GITR-L, 5 galectin-9, 10 and ICOS-ICOS ligand 12 in distinct localization patterns within the tissue. The fact that the immune privileged status of the cornea can be abolished by dysfunction of just one of these molecules suggests that each molecule plays a nonredundant or cooperative role in maintenance of immune privilege.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further elucidate the mechanism of immune privilege for corneal transplantation, further immunologic analysis will be necessary. The cornea constitutively expresses various immune-regulating molecules, such as B7-H1, 8 CD95L, 35,36 GITR-L, 5 galectin-9, 10 and ICOS-ICOS ligand 12 in distinct localization patterns within the tissue. The fact that the immune privileged status of the cornea can be abolished by dysfunction of just one of these molecules suggests that each molecule plays a nonredundant or cooperative role in maintenance of immune privilege.…”
Section: Discussionmentioning
confidence: 99%
“…6 Our group has reported some of the molecules that contribute to ACAID and the immune suppressive ocular microenvironment for establishment of immune privilege for corneal transplantation. B7-H1, 8 glucocorticoid-induced tumor necrosis factor receptor family-related protein ligand (GITR-L), 5,9 galectin-9, 10,11 and inducible costimulatory molecule (ICOS) and ICOS ligand 12,13 are involved in immune suppression in the cornea and are essential for immune privilege for corneal transplantation. The molecular mechanisms of immune privilege in the eye are not fully understood.…”
mentioning
confidence: 99%
“…As shown in Table 1, various immunomodulatory factors are expressed in corneal endothelial cells and in the iris-ciliary body. We have revealed that inhibitory costimulatory signaling molecules such as programmed death ligand-1 (PD-L1, B7-H1) [28], inducible costimulatory molecule ligand (ICOSL, B7-H2, B7-related protein (B7RP)-1) [29], V-domain Ig suppressor of T cell activation (VISTA, PD-1H) [30], glucocorticoid-induced tumor necrosis factor (TNF) receptor family-related protein ligand (GITRL) [31], and galectin-9 [32], are constitutively expressed in the corneal tissue and involved in immune suppression in the cornea (Figure 1). These inhibitory costimulatory signal molecules play an important role in the regulation of antigen-specific T-cell-mediated immune responses.…”
Section: Immune Suppressive Microenvironment In the Anterior Segment mentioning
confidence: 99%
“…ICOS/ICOSL (B7-H2, B7RP-1) signals have been implicated in the differentiation and function of T cells. In the eye, ICOSL mRNA is constitutively expressed in the cornea, iris-ciliary body and retina [29]. Corneal allograft survival in ICOS −/− recipients and wild-type (WT) recipients treated with anti-ICOSL mAb was significantly shorter than in control recipients.…”
Section: Icos Ligand and Icosmentioning
confidence: 99%
See 1 more Smart Citation